GENE-39. CRISPRi-BASED RADIATION MODIFIER SCREEN IDENTIFIES LONG NON-CODING RNA THERAPEUTIC TARGETS IN GLIOMA. (11th November 2019) - John Liu, S; Malatesta, Martina; Seo, Kyounghee; Lien, Brian; Hong, Sung; Koontz, Mark; Raleigh, David; Ullian, Erik; Lim, Daniel
Abstract: Long noncoding RNAs (lncRNAs) exhibit highly cell type-specific expression and function, making this class of transcript attractive for targeted cancer therapy. However, the vast majority of lncRNAs have not been tested as potential therapeutic targets, particularly in the context of currently used cancer therapy. Malignant glioma is rapidly fatal, and ionizing radiation is part of the current standard-of-care used to slow tumor growth in both adult and pediatric patients. Here, we used a CRISPR interference (CRISPRi) platform to systematically screen 5689 lncRNA loci in human glioblastoma (GBM) cells, identifying 467 hits that modified cell growth in the presence of clinically relevant doses of fractionated radiation. 34 of these lncRNA hits sensitized cells to radiation, and based on their expression in adult and pediatric glioma, nine of these hits were prioritized as lnc RNA G lioma R adiation S ensitizers ( lncGRS ). Knockdown of lncGRS-1 – a primate-conserved, nuclear-enriched lncRNA – inhibited the growth and proliferation of primary adult and pediatric glioma cells, but not the viability of normal brain cells. Using human brain organoids comprised of mature neural cell types as a 3-dimensional tissue substrate to model the invasive growth of glioma, we found that antisense oligonucleotides (ASOs) targeting lncGRS-1 selectively decreased tumor growth synergistically with radiation therapy. These studies identify lncGRS-1 as a glioma-specific therapeutic target and establish a generalizable approach to rapidly identify novel therapeutic targets in the vast non-coding genome that can enhance the standard-of-care for cancer therapy.